First report of transfusing low‐titer cold‐stored type O whole blood to an extremely‐low‐birth‐weight neonate after acute blood loss. Issue 9 (25th July 2022) - Carr, Nicholas R.; Hulse, Whitley L.; Bahr, Timothy M.; Davidson, Jessica M.; Ilstrup, Sarah J.; Christensen, Robert D.
Abstract: Background: Multiple reports suggest that cold‐stored low‐titer type O whole blood (LTOWB) is becoming a preferred transfusion product for resuscitating massive hemorrhage across trauma, obstetrical, and pediatric services. However, we know of no reports of using this product for emergency transfusion of newborn infants after acute severe hemorrhage. Case Report: We report our experience with emergency transfusion of re‐warmed LTOWB using a fluid warmer for the resuscitation of a hypotensive 25‐week gestation neonate following acute and severe placental abruption. The transfusion was tolerated well, without evidence of hemolysis or other complications. Conclusions: This is the first report of which we are aware of transfusing warmed LTOWB to a preterm neonate. Our positive experience leads us to speculate that this product could have a role for neonates following acute severe blood loss.